MEKANISME PENGISIAN DAN PENEMPATAN DAN STOPPING DALAM POSISI DI PEMERINTAH DAERAH KOTA SOLOK - Rafles, Johan (UNES Law Review, 2019)
The specification of this study is descriptive analytical with the approach methodused is normative juridical as the main approach and supported by an empirical juridicalapproach, this means taking an approach that emphasizes on the practice of the fieldassociated with the legal aspects or legislation in force. Data sources used primary andsecondary data sources and interviews were analyzed qualitatively with the results ofanalytical descriptive data presentation.Based on the results of the discussion and analysis, it is obtained as follows: First,the mechanism of filling and placement and dismissal in functional positions,administrator positions, and high leadership positions for provisions and procedures aswell as termination of positions are regulated in Government Regulation Number 11 of2017 concerning PNS Management but provisions those that have not been regulated byfurther provisions in this PP can use existing PP provisions which may not becontradictory, including ministerial regulations that regulate technically. Second, theinhibiting factors of the mechanism for filling and placing and terminating positions in theSolok City Regional Government include: not prioritizing competence in occupyingpositions; the merit system has not gone well; Transfer / Transfer of Civil ServantsPosition between Regency / City.